If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + -1b = d + -1cx Reorder the terms: ax + -1b = -1cx + d Solving ax + -1b = -1cx + d Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'b' to each side of the equation. ax + -1b + b = -1cx + b + d Combine like terms: -1b + b = 0 ax + 0 = -1cx + b + d ax = -1cx + b + d Reorder the terms: ax = b + -1cx + d Divide each side by 'x'. a = bx-1 + -1c + dx-1 Simplifying a = bx-1 + -1c + dx-1
| 4x^4-5x^3-2x^2=0 | | -10+6=-7x+-9 | | 3-4x-5=-2 | | 0.25(12+4x)-0.5(8+2x)=0 | | 5x+6y-17=0 | | -8x+3(1-8x)=-4x+31 | | 0.25(12+4x)-0.5(8+2x)= | | x^3*x^6*x^9= | | 5=-3b-4-3 | | 3x^3+16x^2+15x-18=0 | | 11=n/6-5 | | 2x-8=-3x+2 | | 1-3p-1=-18 | | 11-7x=107-28x | | 21=43-2r | | 2(x+3)=x-13 | | 52=5d+7 | | w-22= | | a/12-3=2 | | 2(x+3)+4x=6+6x | | 69-2x=16x+19 | | 1.3(x-13)=14 | | 9x+20y=85 | | 6x^3+7x^2-3x= | | -10x=2x^2 | | .5n+5n=7n-18 | | -5x+8x-33=21 | | (x-9)-(-5+3)=1 | | 0.6(x-13)=14 | | 6x^2+7x^2-3x= | | 10+(-11)+(-12)= | | 3(44)+2r=240 |